Effect of cooling water loop on the thermal performance of air conditioning system. (November 2019) - Siricharoenpanich, A.; Wiriyasart, S.; Prurapark, R.; Naphon, P.
Abstract: The aim of this research is to improve thermal performance of air conditioning system by cooling water loop. In experiment, the cooling water loop with the concentric helically coiled tube heat exchanger is installed between the compressor unit and condenser unit for cooling refrigerant before entering the condenser unit. Effects of water mass flow rate and atmospheric temperature on the COP are considered. The obtained results are compared with those from the conventional air conditioning system without cooling water loop. It can be seen that the COP tends to increase with increasing water mass flow rate and tend to decrease as atmospheric temperature increases. The highest COP is 31.02% as compared with the conventional reference system, respectively. In addition, not only COP of air conditioning system are increased but also the hot water storage is obtained which used for various applications. The results obtained this study are expected to lead to guidelines that will allow the improved thermal performance of air conditioning system and hot water storage system which reduce energy consumption.